Implementation of a project-based scientific approach in IPAS learning for 5th-grade elementary school student - Febbry Oktaviani; Oktaviani Adhi Suciptaningsih; Siti Faizah (Universitas Papua, 2026)
This study aims to analyze the implementation of the Project-Based Scientific Approach (PjBL-SA) in science and social studies learning and its influence on elementary students’ critical thinking skills. Conducted in Grade V of SDN 013 Tana Tidung, this mixed-method research integrated qualitative observations and quantitative testing. Data were gathered through classroom observations, questionnaires, critical thinking tests, and interviews with teachers and students. The results showed that the PjBL-SA model effectively enhanced students’ learning engagement and conceptual understanding. Students reported increased motivation (78%), better comprehension through practice (82%), and higher enjoyment in group learning (75%). Statistical analysis using a paired t-test demonstrated a significant improvement in critical thinking performance (pretest = 62.3; posttest = 78.9; t = 6.24; p < 0.05), with the highest gain in the inference indicator (0.42). Pearson correlation analysis further indicated a strong positive relationship between project involvement and critical thinking (r = 0.63; p < 0.01). These findings confirm that PjBL-SA fosters students’ critical, creative, and collaborative abilities, making it a relevant and innovative instructional strategy for IPAS in elementary education.